When are they old enough to drink? Outcomes of an Australian social marketing intervention targeting alcohol initiation. (4th January 2018) - Jones, Sandra C.; Andrews, Kelly; Francis, Kate L.; Akram, Muhammad
Abstract: Introduction and Aims: This paper reports on the evaluation of an Australian whole‐of‐community social marketing intervention targeting social norms, which aimed to reduce inflated perceptions of the prevalence of underage drinking and increase the age at which alcohol initiation is considered acceptable. Design and Methods: A community‐wide intervention was delivered in a single community over a period of 2 years, targeting adolescents, parents and community members. Pre‐and post‐intervention computer‐assisted telephone interview surveys were conducted in the intervention and a matched comparison (control) community. A total of 417 respondents completed both surveys (215 in the intervention community and 202 in the control community). Results: The intervention community saw an increase of 6 months in the average age at which it is perceived to be acceptable for young people to have a sip/taste of alcohol and 5 months in the average age at which it is perceived to be acceptable to have weak/watered down alcohol. Furthermore, there was a reduction in the perception of the prevalence of alcohol consumption by young people to a level consistent with actual underage drinking rates. In comparison, the control community saw no change in any of these variables. Discussion and Conclusions: This study provides preliminary evidence that a whole‐of‐community social marketing intervention can change perceptions of the prevalence, and acceptability, of underage drinking. Given the central role of social norms in decisions regarding alcohol consumption, these changes have the potential to reduce parental supply and thus underage drinking.